(untitled) (Malaysian Journal of Applied Linguistics (MJoAL), 2023)
ABSTRACT The current study seeks to determine the association between attitude and public speaking anxiety in the context of learning English by using a correlational research approach. A non-probability sampling approach was utilised to recruit the participants. Among four government universities in Malaysia, 191 Jordanian postgraduate students (PhD candidates) were chosen. The following two surveys were used to gather the data: (a) Foreign Language Classroom Anxiety Scale (FLCAS); and (b) Attitude/Motivation Test Battery (AMTB). A correlational analysis was performed using Smart PLS 3.0 to test the hypotheses. The results show that attitude is substantially associated with English public speaking anxiety. It appears that among PhD students in Jordan, there is a strong negative association between attitude and public speaking anxiety in English. The findings have potential implications on language motivation and classroom instruction in foreign language settings.